GESTÃO ESCOLAR: fundamentos e práticas em escolas da rede municipal de ensino de São Luís-MA. - Dublante, Carlos André Sousa (2009)
This paper has the theme "School Management: foundations and practices in schools in the municipal teaching in São Luis-MA." It aims to analyze the practices of management in municipal public schools in São Luis, highlighting in its bases the influence of State‟s reformation and, consequently, the educational reforms in the development of all the school's actions. It uses as a parameter of analysis the Political-Pedagogical Project (PPP) and operation of School Councils. Researches were carried out in three schools in which we analyzed the PPP in its documentary form, the Internal Bylaws of municipal school network, the Regulations and the Acts of the School Councils. Consolidating these reviews the principals, teachers, parents and school children were interviewed. The legal basis that underlies the exercise of democratic management in public schools are highlighted, taking as a starting point the school community participation in the management and actions of the school. Data collected through document reviews and interviews are presented, proving that even before the existence of several mechanisms allowing for democratic practices in school management, yet authoritarian features and centralizing actions remain. Finally, we analyze the process of preparation and participation of segments of the school (administrators, teachers, parents and students) in implementing the PPP, and also how the composition of School Councils, as well as their participation in the management of the school.